N-type conjugated polymer as efficient electron transport layer for planar inverted perovskite solar cells with power conversion efficiency of 20.86%. (February 2020) - Chen, Wei; Shi, Yongqiang; Wang, Yang; Feng, Xiyuan; Djurišić, Aleksandra B.; Woo, Han Young; Guo, Xugang; He, Zhubing
Abstract: Fullerene and its derivatives are commonly used as electron transport layers (ETLs) in inverted perovskite solar cells (PSCs), since they show suitable band alignment and good electron mobility. However, fullerene-based ETLs typically result in low open-circuit voltages due to the interfacial defects, and they also exhibit poor photochemical and thermal stability. Consequently, there is great interest in the development of novel ETLs for high-performance inverted PSCs. In this work, two n-type polymers PBTI and PDTzTI are utilized as ETL in inverted PSCs, which are based on bithiophene imide and thienylthiazole imide, respectively. Due to its high electron mobility, well matched energy level alignment together with the passivation of interfacial traps/defects, device with the PDTzTI ETL demonstrates a best power conversion efficiency of 20.86%, which outperform those with PBTI and PCBM ETLs. Owning to the highly hydrophobic properties as well as the mobile ion blocking capability of polymer, PDTzTI ETL based device also exhibits excellent long-term and operational device stability as compared with the PCBM one. Our results demonstrate that rational selection of ETLs has great impact on the device efficiency and stability in inverted planar PSCs and that novel n-type polymer might be ideal alternative ETL in inverted planar PSCs. Graphical abstract: Image 1 Highlights: Two N-type polymers PBTI and PDTzTI have been successfully used as ETL in inverted planar PSCs. PSCs with the PDTzTI ETL demonstrate a best power conversion efficiency of 20.86%, which outperform those with PBTI and PCBM ETLs. High electron mobility, better energy level alignment and the interfacial defects passivation account for the performance improvement. PDTzTI ETL based devices exhibit excellent long-term and operational stability as compared with the PCBM one.